Primary chaetotaxy and larval morphometry of Phaenonotum exstriatum and Dactylosternum cacti (Coleoptera: Hydrophilidae) - Archangelsky, Miguel (2016)
The primary and secondary chaetotaxy of the head capsule and head appendages of the three larval instars of Dactylosternum cacti (LeConte, 1855) and Phaenonotum exstriatum (Say, 1835) (Coleoptera: Hydrophilidae: Sphaeridiinae) are described for the fi rst time. Morphometric characters derived from the head capsule, mouthparts and legs are also included, together with detailed illustrations of all characters. Morphology and chaetotaxy of these larvae are compared to that of other described Coelostomatini larvae.